Potential of Streptomyces spp. From Peanut Plant Soil as an Entomopathogen of Pests Spodoptera Litura - Ferdianto Eko Wicaksono; Wiwin Windriyanti; Penta Suryaminarsih (Demeter: Journal of Farming and Agriculture, 2024)
Peanuts are agricultural commodities that have high economic value and play an important role in meeting human needs, namely as a source of vegetable protein, oil and other nutrients, but domestic peanut production has not been able to meet the needs of the Indonesian people. The national demand for peanuts reaches 856.1 thousand tons per year, and the average consumption of peeled peanuts is 0.32 kg per capita every year. [1] In 2013 peanut production was 701,680 tons, then there was a decrease in production in 2014 to 638,896 tons, and continued until 2015 to 605,449 tons, thus showing a 13.7% decrease that occurred from 2013 to 2015. Low productivity is caused by various factors, one of which is the attack of pests and plant diseases. This study aims to determine the type of Streptomyces spp. Microbes with high chitinolytic content that can control armyworm pests (S.litura) on peanut plants. and influence of biological control agency Streptomyces spp as an entomopathogen of insect pests S. litura. This study was able to improve understanding of the influence of the biological control agency Streptomyces spp as an entomopathogen of S. litura insect pests to protect plants in the future. The results of the exploration of Streptomyces sp. acquired Colonies are irregular and branched coccus-shaped. The colony is tightly attached to the GNA medium, wavy white with a notched surface and a starchy texture. In addition, it has the largest chitinase enzyme content with a chitin zone diameter of 3 cm. PCR test Based on BLAST® result tabulation data that isolates belong to the genus Streptomyces sp. with an identity percentage of 99.86% with Streptomyces sp. VEL gene 17 to 16 rRNA, partial sequence with access code AB914463.2 The highest mortality was in the treatment (S0 RP K3) and (S1 RP K3) there was 60% this showed that with the administration of Streptomyces sp. With a concentration of 75% can cause very high mortality with abdominal contact poison in S. Litura pests